IS THERE A SAFE TUMOR SIZE FOR IDENTIFICATION OF BREAST CARCINOMA WITHOUT AXILLARY NODE METASTASIS? - Vieira, René Aloisio da Costa; Oliveira-Junior, Idam de; Cavalin, Thaissa Daud de Faria; Tabuti, Rhaissa Iara Magano; Costa, Allini Mafra da; Netto, Jorge Nahas (Mastology, 2019)
Objective: To evaluate the rate of absence of axillary pathological involvement in patients with clinically negative axilla, submitted to axillary lymphadenectomy (AL). Method: Retrospective longitudinal study, which clinically evaluated patients without axillary metastasis (cN0), who underwent oncologic treatment from 1998 to 2001. Patients were selected at clinical stage I to III. The axillary pathological impairment ratio was correlated with tumor size and clinical stage T and TNM. We also evaluated the locoregional and axillary (local) recurrences. Results: 519 clinically cN0 patients were selected. All were submitted to AL, with a mean of 18 lymph nodes dissected and 3.2 compromised. The axillary metastatic rate was 47.2%. Tumor size and clinical stage were associated with the presence of axillary lymph node metastasis (p<0.001). The axillary involvement was of 78.6% for tumors between 6.1 to 8 cm, and of 100% for tumors larger than 8.1 cm. Forty patients were T4- TNM, where the impairment rate was 57.5%. The specific survival at 120 months was 71.1%, with locoregional recurrence rate of 6.9% (n=36) and local rate of 0.4% (n=2). Conclusion: In patients submitted to axillary lymphadenectomy, the axillary recurrence was extremely low. There are patients with tumors greater than 5 cm, smaller than 8 cm, and selected T4-TNM without metastasis in axilla. Further studies are necessary to evaluate sentinel lymph node dissection in this selected group, but it is unacceptable for tumors larger than 8.1 cm.